2020
DOI: 10.1038/s41598-020-64155-5
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic LPS binding peptide 19-2.5 interferes with clotting and prevents degradation of high molecular weight kininogen in plasma

Abstract: Sepsis and septic shock are life-threatening conditions and remain an important medical problem, emphasizing the need to identify novel therapeutic approaches. Coagulation dysfunction, hypotension, disturbed microcirculation and multiorgan failure occur frequently. These severe conditions result from an overwhelming inflammatory response, induced by pathogen and damage associated molecular patterns (PAMPs and DAMPs) released into the bloodstream. In the present study, we demonstrated that the synthetic Lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It has been shown that the induction of procoagulant activity in blood or PBMCs by LPS and other PAMPs is associated with the release of pro- and anti-inflammatory cytokines [27, 37, 38]. We therefore measured IL-6, IL-10, and TNFα in the supernatant of PBMCs, treated with pneumolysin or autolysin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the induction of procoagulant activity in blood or PBMCs by LPS and other PAMPs is associated with the release of pro- and anti-inflammatory cytokines [27, 37, 38]. We therefore measured IL-6, IL-10, and TNFα in the supernatant of PBMCs, treated with pneumolysin or autolysin.…”
Section: Resultsmentioning
confidence: 99%
“…PBMCs were isolated using diluted blood (1:1 in PBS) from healthy volunteers as described [27]. The PBMC cell layer was collected, and cells were washed twice in PBS and resuspended in RPMI medium (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been proposed to search for well-conserved parts of the endotoxin, and a promising candidate could be part of the inner core region called 3-deoxy-D-manno-octulosonic acid (KDO) [45], or the lipid A with fully synthetic disaccharide lipid A mimetics (DLAMs) [46]. Among these peptides, we report, as an example, the LPS-binding peptide 19-2.5, which not only interferes with the activation of the coagulation and contact system but also prevent the interaction of LPS with the high molecular weight kininogen (HK), one of the major LPS carriers in blood [200].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Furthermore, it demonstrates very low cytotoxicity and can reduce the level of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) [64] as well as to attenuate cardiomyopathy in the septic heart [65,66]. Lately, it has been reported that this peptide also inhibits activation of the intrinsic coagulation pathway by significantly reducing the activity of Factor XI [67]. Recently, the high binding affinity of Pep19-2.5 towards Gram-positive and Gram-negative bacteria was explored for capturing bacteria in liquid samples [68].…”
Section: Introductionmentioning
confidence: 99%